Indoor microbial growth prediction using coupled computational fluid dynamics and microbial growth models - Oladokun, Majeed; Ali, Maisarah; Osman, Samsul Bahrin (2015)
This study investigates, using in-situ and numerical simulation experiments, airflow and hygrothermal distribution in a mechanically ventilated academic research facility with known cases of microbial proliferations. Microclimate parameters were obtained from in-situ experiments and used as boundary conditions and validation of the numerical experiments with a commercial CFD analysis tool using the standard k–ε model. The findings revealed good agreements with less than 10% deviations between the measured and simulated results. Subsequent upon successful validation, the model was used to investigate hygrothermal and airflow profile within the shelves holding stored components in the facility. The predicted in-shelf hygrothermal profile were superimposed on mould growth limiting curve earlier documented in the literature. Results revealed the growth of xerophilic species in most parts of the shelves. The mould growth prediction correlates with the microbial investigation in the case studied room reported by the authors elsewhere. Satisfactory prediction of mould growth in the room successfully proved that the CFD simulation can be used to investigate the conditions that lead to microbial growth in an indoor environment. Keywords Hygrothermal performance; in-situ experiments; microbial growth prediction; CFD simulation; indoor microclimate.